The high-order cyclotron modes in Fermi liquid of Q2D layered conductors - Kirichenko, O.V.; Peschansky, V.G.; Stepanenko, D.I. (Condensed Matter Physics, 2005)
The propagation of electromagnetic waves in layered conductors at the presence of an external magnetic field is investigated theoretically. At certain orientations of a magnetic field concerning the layers of the conductor the collisionless absorption is absent and weakly damping collective modes can propagate even under the strong spatial dispersion. In a short-wave limit the existence of electromagnetic waves with frequencies near the cyclotron resonances is possible at an arbitrary orientation of the wave vector with respect to an external magnetic field. We have obtained the spectrum of waves with the frequencies near the cyclotron resonances of high order with regard to the Fermi-liquid interaction of the electrons.